Water quality study at Lebir River cause by flood event and sedimentation process - Siti Syuhaida, Adnan (2016)
Lebir River is one of the main tributary of Kelantan River and has been spotted that which has high potential rate affected by flood. A research was conducted as to calculate the total sediment load at Lebir River, analyze the water quality of Lebir river due to flood event and sedimentation process and to identify the relationship between amounts of sediment load with water quality in the river. Five stations were setting up for the collection of sample of sedimens and water samples which are situated at downstream, Kg Lebir, Paloh (Station 1), Kg Manek Urai Lama (Station 2), middle stream,Kg Laloh (Station3), Kg Bukit Tebuk (Station 4) and upstream, Kg Ladang Lapan Kabu (Station 5) along the Lebir River on October 2015. The particle size for sediments was distributed in the range of 0.063mm to 5mm by using sieve analysis method. Engelund/Hansen function method was used for the prediction of the total sediment load at Lebir River. Besides that, analysis of water quality at Lebir River was conducted based on six parameters (Biochemical Oxygen Demand, Chemical Oxygen Demand, Dissolved Oxygen Total Suspended Solid, Ammoniacal Nitrogen, pH and Turbidity). From overall findings, the sediment size at Station 1, 2, 3 and 4 retained 1.18mm and found as coarse sand type (0.5-2.0mm) and for Stations 5 retained on the size 5mm which indicates the fine gravel types. For the prediction of total sediment loads, Station 1 has 13737.6tonnes/m-day, Station 2 has 16243.2 tonnes/m-day, Station 3 has 7516.8 tonnes/m-day, Station 4 has 3801.6 tonnes/m-day and Station 5 has 518.4 tonnes/m-day. Based on analysis of water quality at Lebir River, the river is in Class IV which is in range (34.35 to 51.59) after flood compare to Class II before flood event. Biochemical Oxygen Demand, Chemical Oxygen Demand, Dissolved Oxygen Total Suspended Solid, Ammoniacal Nitrogen, pH and Turbidity shows the higher value than the value before flood event.